The green book the everyday guide to saving the planet one simple step at a time - Rogers, Elizabeth (Elizabeth Kendall) 1965-; Kostigen, Thomas (Three Rivers Press, 2007)
Ellen DeGeneres, Robert Redford, and other celebrities tell you how they make a difference to the environment. With wit and authority, authors Rogers and Kostigen provide hundreds of solutions for all areas of your life, pinpointing the smallest changes that have the biggest impact on the health of our precious plane, such as: If everyone in the United States refused their ATM receipts, it would save a roll of paper more than two billion feet long. If everyone in America turned off the tap while brushing their teeth, the daily savings could add up to more water than is consumed in all of New York City. If all answering machines in U.S. homes were replaced by voice-mail services, the annual energy savings would be equivalent to removing 250,000 cars from the road.--From publisher description.